Which Method for Diagnosing Small Fiber Neuropathy? - Fabry, Vincent; Gerdelat, Angélique; Acket, Blandine; Cintas, Pascal; Rousseau, Vanessa; Uro-Coste, Emmanuelle; Evrard, Solène M.; Pavy-Le Traon, Anne (Frontiers in Neurology, 2020)
Introduction: Small fiber neuropathies (SFN) induce pain and/or autonomic symptoms. The diagnosis of SFN poses a challenge because the role of skin biopsy as a reference method and of each neurophysiological test remain to be discussed. This study compares six methods evaluating small sensory and autonomic nerve fibers: skin biopsy, Quantitative Sensory Testing (QST), quantitative sweat measurement system (Q-Sweat), Laser Evoked Potentials (LEP), Electrochemical Skin Conductance (ESC) measurement and Autonomic CardioVascular Tests (ACVT). Methods: This is a single center, retrospective study including patients tested for symptoms compatible with SFN between 2013 and 2016 using the afore-mentioned tests. Patients were ultimately classified according to the results and clinical features as “definite SFN,” “possible SFN” or “no SFN.” The sensitivity (Se) and specificity (Sp) of each test were calculated based on the final diagnosis and the best diagnostic strategy was then evaluated. Results: Two hundred and forty-five patients were enrolled (164 females (66.9%), age: 50.4 ± 15 years). The results are as follows: skin biopsy: Se = 58%, Sp = 91%; QST: Se = 72%, Sp = 39%; Q-Sweat: Se = 53%, Sp = 69%; LEP: Se = 66%, Sp = 89%; ESC: Se = 60%, Sp = 89%; Cardiovascular tests: Se = 15%, Sp = 99%. The combination of skin biopsy, LEP, QST and ESC has a Se of 90% and a Sp of 87%. Conclusion: Our study outlines the benefits of combining skin biopsy, ESC, LEP and QST in the diagnosis of SFN.